Using team service-learning projects in environmental science - Sanford, Robert M. (Groupwork, 2012)
This paper describes the rationale and means used to guide students in developing, presenting, and assessing civic engagement projects done as teams. Team projects and other forms of groupwork are effective tools for improving student learning. This paper presents a ‘roadmap’ of different environmental courses with descriptions of possible group products, evaluation schemes for effective grading, and forms of student feedback. Team learning promotes creative, dynamic responses to community opportunities. The result of team learning enhances student performance and skills, in addition to benefitting the community.